Motivational traits: An objective behavioral test using a computer game - Fernández-Avilés, Daniel; de Antonio, Angélica; Villalba-Mora, Elena (Frontiers in Psychology, 2022)
An objective behavioral test for motivational traits has been developed taking as a reference the structure of the Motivational Trait Questionnaire, which is a validated self-report questionnaire to measure motivational traits in the population. The objective test consists of a computer game, which makes it possible to evaluate a person's motivational traits and to display them on the same scale as the Motivational Trait Questionnaire. In order to evaluate the validity of the results obtained in the measurement of motivational traits by the objective behavioral test, a study was carried out with 31 participants whose motivational traits were assessed by the two methods, and the results obtained were compared in order to find out whether the two forms of assessment can be considered equivalent. Statistical tests support the high degree of similarity of the results, concluding that the objective behavioral test can be a useful instrument to assess motivational traits as an alternative to the self-report questionnaire.